LANGUAGE FUNCTIONS AS PRAGMATIC STRATEGIES IN TIKTOK LIVE SELLING - Yulia Febrianti Putri; Diana Rozelin; Erwin Hage (ELITERATE : Journal of English Linguistics and Literature Studies, 2026)
Language functions are fundamental to human communication because they enable speakers to convey information, express emotions, maintain social interaction, and influence others in different communicative contexts. These functions have become increasingly important in live-streaming commerce, particularly on TikTok Live, where sellers are expected to provide product information while simultaneously engaging viewers and encouraging purchasing decisions through real-time interaction. Although previous studies have explored persuasive communication, pragmatics, and consumer behavior in live-streaming commerce, limited attention has been devoted to examining how language functions operate collectively as pragmatic strategies in owner-hosted TikTok Live selling sessions. Therefore, this study aims to investigate the language functions employed by the owner-host of Boss Up Cosmetic during TikTok Live selling and to examine how these functions support persuasive communication. This study employed a qualitative descriptive approach by analyzing 153 utterances collected from recorded TikTok Live sessions conducted between July and October 2025. The data were transcribed, classified according to Jakobson's (1960) six language functions, and analyzed using qualitative content analysis. The findings revealed that all six language functions were employed during the live-selling sessions, with the conative function occurring most frequently, followed by the referential, phatic, emotive, metalingual, and poetic functions. These findings indicate that language functions operate collectively as pragmatic strategies that not only provide product information but also strengthen audience engagement and encourage purchasing decisions during TikTok Live selling. Consequently, this study extends the application of Jakobson's theory to digital commerce and contributes to the growing body of research on pragmatics in live-streaming communication.